The Lesson Plans Of History Teachers Based On The 2013 Curriculum At Public Senior High School 1 Of Jember (International Journal of Scientific Research and Management (IJSRM), 2018)
This article is intended to describe the lesson plans developed by History subject teachers at SMA Negeri 1 Jember. The design of this research was interactive qualitative with the ethnographic design of case studies, assessment based on the analysis of interview results, observations, documents, and questionnaires. The data source under investigation was both primary and secondary data. The results of this research showed that at the lesson planning stage, the History teachers who were members of the MGMP school team developed independent lesson plans in accordance with the class level they taught. The preparation of lesson plans was carried out at the beginning of the semester or new academic year during in-house training and on-house training. The analysis of the lesson plans components showed that the lesson plans developed by each History teacher were in accordance with the provisions. The average score of 89 lesson plans was 131 or 73%. The composition of the lesson plans components referred to the process standard in The Regulation of Ministry of Education and Culture No. 81A of 2013, The Regulation of Ministry of Education and Culture No. 103 of 2014, and The Regulation of Ministry of Education and Culture No. 22 of 2016.